1967
DOI: 10.1139/o67-042
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Action on Monoamine Oxidase Activity in Rats

Abstract: Male young and adult rats were injected with thyroxin, hydrocortisone and puromycin. Monoamine oxidase (MAO) activity was studied in liver, brain, kidney, and heart with L-tryptamine-2-14C as substrate. After thyroxin treatment, heart MAO increased in young animals but decreased in adult animals. Thyroxin decreased liver MAO in adult animals. Brain MAO remained constant in all experiments, whereas kidney MAO showed a slight decrease after thyroxin injection. In young rats, puromycin did not prevent the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Although there is no direct evidence for such an effect, modulation of membrane potential in other neuronal populations by glucocoticoids has been reported and these effects, consistently with our findings, depend on background electrical activity (9). Second, glucocorticoids may decrease dopamine catabolism by acting as a reversible monoamino oxidase inhibitor (23)(24)(25). This effect is consistent with the fact that administration of synthetic glucocorticoids decreases deaminated products of dopamine, such as HVA and DOPAC (25,26), that depend on monoamino oxidase activity, while increasing 3MT levels (25).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although there is no direct evidence for such an effect, modulation of membrane potential in other neuronal populations by glucocoticoids has been reported and these effects, consistently with our findings, depend on background electrical activity (9). Second, glucocorticoids may decrease dopamine catabolism by acting as a reversible monoamino oxidase inhibitor (23)(24)(25). This effect is consistent with the fact that administration of synthetic glucocorticoids decreases deaminated products of dopamine, such as HVA and DOPAC (25,26), that depend on monoamino oxidase activity, while increasing 3MT levels (25).…”
Section: Discussionsupporting
confidence: 79%
“…Glucocorticoids share the neurochemical actions of psychostimulants in that they both increase extracellular concentrations of dopamine (this paper) and both seem to exert this effect through inhibition of dopamine reuptake and inhibition of monoamino oxidase activity (23)(24)(25)(26)(27)(28)(29). At the behavioral level, corticosterone induces self-administration (19) and dopamine-dependent locomotor activity as do psychostimulants (30).…”
Section: Discussionmentioning
confidence: 86%
“…Effects of corticosterone on TH have been demonstrated in the locus coeruleus (24), hypothalamus (25), and more recently in the VTA (26), though important individual differences in the latter effects have been reported (26). Second, glucocorticoids may decrease dopamine catabolism acting as reversible monoamine oxidase inhibitors (27)(28)(29). This action of glucocorticoids is consistent with the fact that dexamethasone decreases deaminated products of dopamine such as HVA and DOPAC (29,30), which depend on monoamine oxidase activity, whereas it increases 3MT levels that depend on COMT (catechol-O-methyltransferase) (29).…”
Section: Discussionmentioning
confidence: 99%
“…cardiac MAO activity was increased in hyper thyroid rats or by administration of thyro mimetic compounds (10, 13,14). However, in this study, it was confirmed that MAO activity in heart, lung and liver mitochondria decreased repidly to about 50% that of the control values on the first days; and after that, heart MAO activity increased gradually and completely restored to the control value after 10 days, although it has been reported that there is a continous increase of cardiac MAO activity with age and weight in male rats up to 16 weeks of age (10, 18).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there have been reports which show an increase of hepatic MAO activity by in thyroid-fed rats (11) and no measurable change in myocardiac MAO activity following administration of thyromimetic compounds (12). However, these discrepancies in the measurements of MAO activity depend on the sex and age of the animals used (7, 10, 13,14).…”
mentioning
confidence: 99%